Capital Structure and Financial Performance of Firms: Evidence from Vietnam - Ngoc Minh, Ngo (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the impact of capital structure on the financial performance of listed firms on the Hanoi stock exchange, the second biggest stock market in Vietnam. The paper uses pooled ordinary least squares (Pooled OLS), fixed effect models (FEM), and random effect models (REM) to process the panel data for the period 2015-2019. The results show that capital structure negatively affects financial performance, which is represented by three indicators: return on equity (ROE), return on total assets (ROA), and earnings per share (EPS). On the other hand, firm size positively impacts ROA and EPS, while growth opportunities and asset structure negatively affect ROE and ROA.